A virtual simulation-based training program on birthing positions: a randomized controlled trial - Huimin Lin; Guihua Liu; Xiaoyan Wang; Qin Xu; Shengbin Guo; Rongfang Hu (BMC, 2023)
Abstract Background Restricting parturient women in healthcare facilities from choosing positions that provide the greatest comfort and benefit during labor is a global barrier. Several complex factors, including caregiver preference and medical intervention, shape the limitation. Therefore, a practical need exists to train midwives on the knowledge and skills to change this condition. Methods The study used a parallel, single-blind, randomized controlled trial at a provincial maternity and child health hospital in Fujian, China, from June 1 to December 31, 2019. The midwives in a birth suite were selected and randomly enrolled in a one-month simulation-based hybrid training or face-to-face teaching in September 2019. The four-level Kirkpatrick's model, including reaction, learning, behavior, and results, was used to evaluate training effects before and after the program. Data were analyzed with SPSS 25.0 using Student's t-test, Spearman's correlation test, Mann-Whitney U test, Wilcoxon signed-rank test, and chi-square test analysis of variance. The significance level was set at p < 0.05. Results Forty-two midwives were initially randomized to either the virtual simulation group or the face-to-face group. One midwife was excluded from the analysis due to intervention discontinuation, resulting in a final analysis of 41 midwives (n1 = 21, n2 = 20). Post-intervention, the virtual simulation group exhibited higher satisfaction and learning effects compared to the face-to-face group, while the rate of perineal incision in primiparas was lower (p<0.05). No significant changes or differences were observed in self-rated behavior between the two groups (p>0.05). The virtual simulation group demonstrated an increase in non-supine birth rate (p = 0.030) and a decrease in perineal incision rate among primiparas compared to pre-intervention (p = 0.035). Moreover, knowledge performance was associated with the duration of virtual simulation (r = 0.664, p = 0.001). Conclusions Virtual simulation is a fascinating innovation that enables midwives to develop birthing positions without practicing on real pregnant women and is one solution to achieve work competency within a shortened training period.